2016
DOI: 10.1109/tmi.2016.2547947
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Classification of Gastrointestinal Lesions in Regular Colonoscopy

Abstract: We have developed a technique to study how good computers can be at diagnosing gastrointestinal lesions from regular (white light and narrow banded) colonoscopic videos compared to two levels of clinical knowledge (expert and beginner). Our technique includes a novel tissue classification approach which may save clinician's time by avoiding chromoendoscopy, a time-consuming staining procedure using indigo carmine. Our technique also discriminates the severity of individual lesions in patients with many polyps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(114 citation statements)
references
References 77 publications
2
112
0
Order By: Relevance
“…cancer) actomyosin meshwork pattern(s). 3,28,29 Human colon epithelium demonstrates various patterns during colonoscopy that correlate with different physiological and pathological conditions, which can be recognized using recently developed artificial intelligence algorithms. 16,29 2D/3D patterns consistent with Turing's hypothesis appear to be present in our clinical data set (Figure 2A).…”
Section: Functional Bowel Disorders (Fbd) and Colorectal Cancersupporting
confidence: 86%
See 1 more Smart Citation
“…cancer) actomyosin meshwork pattern(s). 3,28,29 Human colon epithelium demonstrates various patterns during colonoscopy that correlate with different physiological and pathological conditions, which can be recognized using recently developed artificial intelligence algorithms. 16,29 2D/3D patterns consistent with Turing's hypothesis appear to be present in our clinical data set (Figure 2A).…”
Section: Functional Bowel Disorders (Fbd) and Colorectal Cancersupporting
confidence: 86%
“…Therefore, it is feasible to combine these techniques to assess tight junction geometric patterns potentially useful to monitor the transformation of normal to abnormal (e.g. cancer) actomyosin meshwork pattern(s) . Human colon epithelium demonstrates various patterns during colonoscopy that correlate with different physiological and pathological conditions, which can be recognized using recently developed artificial intelligence algorithms .…”
Section: Some Potential Applications Of Turing Pattern Analysis In Gasupporting
confidence: 75%
“…However, the strength of this proposed system is that it utilizes more than 100 standard videos from different sources including its own dataset. Most of the data have been collected from Department of Electronics, University of Alcala (http://www.depeca.uah.es/colonoscopy_dataset/) [16]. Another important source of data set is Endoscopic Vision Challenge (https://polyp.grand-challenge.org/databases/) [22].…”
Section: Resultsmentioning
confidence: 99%
“…In case of the rectal cancer diagnosis, most studies have been mainly based on the hand‐crafted features such as features from vessels structures and from local patches . As above mentioned, these methods have limitation that they require researcher's knowledge such as the selection of the region‐of‐interest (ROI) for rectal tumor.…”
Section: Introductionmentioning
confidence: 99%
“…In case of the rectal cancer diagnosis, most studies have been mainly based on the hand-crafted features such as features from vessels structures and from local patches. [17][18][19][20] As above mentioned, these methods have limitation that they require researcher's knowledge such as the selection of the region-of-interest (ROI) for rectal tumor. Recently, some studies have reported successful results for applying deep learning technology to colorectal and rectal cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%